The chronostratigraphy of the Haua Fteah cave (Cyrenaica, northeast Libya) — Optical dating of early human occupation during Marine Isotope Stages 4, 5 and 6. Issue 105 (April 2017) - Jacobs, Zenobia; Li, Bo; Farr, Lucy; Hill, Evan; Hunt, Chris; Jones, Sacha; Rabett, Ryan; Reynolds, Tim; Roberts, Richard G.; Simpson, David; Barker, Graeme
Abstract: The paper presents the results of optical dating of potassium-rich feldspar grains obtained from the Haua Fteah cave in Cyrenaica, northeast Libya, focussing on the chronology of the Deep Sounding excavated by Charles McBurney in the 1950s and re-excavated recently. Samples were also collected from a 1.25 m-deep trench (Trench S) excavated during the present project below the basal level of the Deep Sounding. Optically stimulated luminescence (OSL) data sets for multi-grain, single aliquots of quartz for samples from the Middle Trench were previously published. Re-analyses of these OSL data confirm significant variation in the dose saturation levels of the quartz signal, but allow the most robust OSL ages to be determined for comparison with previous age estimates and with those obtained in this study for potassium-rich feldspars from the Deep Sounding. The latter indicate that humans may have started to visit the cave as early as ∼150 ka ago, but that major use of the cave occurred during MIS 5, with the accumulation of the Deep Sounding sediments. Correlations between optical ages and episodes of "Pre-Aurignacian" artefact discard indicate that human use of the cave during MIS 5 was highly intermittent. The earliest phases of human activity appear to have occurred during interstadial conditions (5e and 5c), with a later phase of lithic discard associated with more stadial conditions, possibly MIS 5b. We argue that the "Pre-Aurignacian" assemblage can probably be linked with modern humans, like the succeeding "Levalloiso-Mousterian" assemblage; two modern human mandibles associated with the latter are associated with a modelled age of 73–65 ka. If this attribution is correct, then the new chronology implies that modern humans using "Pre-Aurignacian" technologies were in Cyrenaica as early as modern humans equipped with "Aterian" technologies were in the Maghreb, raising new questions about variability among lithic technologies during the initial phases of modern human dispersals into North Africa.